Resultados de las prospecciones magnética y eléctrica del yacimiento arqueológico El Caño (NA-20), Gran Coclé, Panamá - Mojica, Alexis; Mayo, Carlos; Chantada, José Ramón; Gracia, Guillermina Itzel De; Florsch, Nicolas; Mayo, Julia (Revista Española de Antropología Americana, 2007)
In this work we have presented the results of the application of the geophysical methods that we have used for the location of Pre-Columbian features in El Caño (NA-20) archaeological site. In this place we have made magnetic and electrical surveys with the objective of detecting accurately the organization and space configuration of this occupation and the degree of anthropogenic disturbance recent product of the agrarian activity and non-professional excavations.